EGFR inhibition by (-)-epigallocatechin-3-gallate and IIF treatments reduces breast cancer cell invasion. Issue 3 (17th May 2017) - Farabegoli, Fulvia; Govoni, Marzia; Spisni, Enzo; Papi, Alessio
Abstract : Epidermal growth factor receptor (EGFR) expression is an important marker in breast carcinoma pathology and is considered a pivotal molecule for cancer cell proliferation, invasion and metastasis. We investigated the effects of epigallocatechin-3-gallate (EGCG), the most active green tea catechin, in combination with 6-OH-11-O-hydroxyphenanthrene (IIF), a synthetic retinoid X receptor-γ (RXRγ) agonist, on three breast carcinoma cell lines: MCF-7, MCF-7TAM and MDA-MB-231. EGFR and AKT activation and molecular markers of cell motility and migration (CD44, extracellular matrix metalloproteinase (MMP) inducer (EMMPRIN), MMP-2, MMP-9 and tissue inhibitor of metalloproteinases (TIMPs)) were studied after EGCG and IIF treatments. The EGCG + IIF treatment was the most active in down-regulating EGFR phosphorylation at Tyr 1068 in all the investigated cell lines; p473AKT was also down-regulated in MCF-TAM cells. EGCG + IIF was also the most active treatment in reducing the expression of markers of invasion and migration in all the three cell lines: CD44, EMMPRIN, MMP-2 and -9 expression decreased, whereas TIMPs were up-regulated. Zymography and scratch assay also confirmed the reduced invasion tendency. We considered that EGCG and IIF treatments could alter the molecular network based on EGFR, CD44 and EMMPRIN expression interdependence and reduced the migration tendency in MCF-7, MCF-7TAM and MDA-MB-231 cells. These events only occurred in association with AKT inactivation in MCF-7TAM cells. In conclusion, the combination of EGCG and IIF significantly attenuated the invasive behaviour of breast carcinoma cells.